ANALISI MOTIVASI, KEPUASAN, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PT AYU SEPTA PERDANA) - Trisnanda, Yogi (Universitas Labuhanbatu, 2021)
This study aims to determine and analyze motivation, satisfaction, work discipline and work experience on the performance of the employee's case study PT, Ayu Septa Perdana. The population in this study were employees who worked at PT. Ayu Septa Perdana as many as 108 people. This study used a research instrument in the form of a questionnaire with a total sample of 52 respondents. Sampling in this study using the Slovin formula. In simultaneous testing (Test F), it is known that differentiation of motivation, satisfaction, work discipline and work experience simultaneously has a significant effect on employee performance. Partially (t test) it is known that satisfaction differentiation has a positive and significant effect on employee performance, while motivation differentiation, work discipline and work experience have a positive but insignificant effect. Based on the Adjusted R square value of 0.281 or 28.1%, it shows that simultaneously motivation, satisfaction, work discipline and work experience on employee performance is 28.1%, while the remaining 71.9% is explained by other variables not proposed in this study. . Testing the feasibility of research instruments and descriptive analysis of the characteristics of respondents using SPSS (Statistical Package For The Social Science) software Version 20.